High-Dimensional Chaotic System and Its Circuit Simulation - Jianming Liu (Institute of Advanced Engineering and Science, 2013)
The chaotic system plays an important role in electronic and electrical equipment, computer cryptography, computer communication and so on. In this paper, we established three new six-dimensional complex chaotic systems and one new ten-dimensional complex chaotic system. The regularity to generate high-dimensional chaotic system is also found by overlaying a series of low-dimensional chaotic systems with Duffing chaotic system. The circiuts of the new high-dimensional complex chaotic system are designed. The simulation experiments of the high-dimensional complex chaotic circuits are tested. The results of theoretical analysis and experiment show that new high-dimensional complex chaotic systems and their circiuts have the hyperchaotic characteristics. DOI: http://dx.doi.org/10.11591/telkomnika.v11i8.3076